Trade Policy Responses to the COVID-19 Pandemic Crisis : Evidence from a New Data Set - Evenett, Simon; Fiorini, Matteo; Fritz, Johannes; Hoekman, Bernard; Lukaszuk, Piotr; Rocha, Nadia; Ruta, Michele; Santi, Filippo; Shingal, Anirudh (World Bank, Washington, DC, 2020)
This paper presents new high-frequency data on trade policy changes targeting medical and food products since the beginning of the COVID-19 pandemic, documenting how countries used trade policy instruments in response to the health crisis on a week-by-week basis. The data set reveals a rapid increase in trade policy activism in February and March 2020 in tandem with the rise in COVID-19 cases, but also uncovers extensive heterogeneity across countries in their use of trade policy and the types of measures used. Some countries acted to restrict exports and facilitate imports, others targeted only one of these margins, and many did not use trade policy at all. The observed heterogeneity suggests numerous research questions on the drivers of trade policy responses to COVID-19, the effects of these measures on trade and prices of critical products, and the role of trade agreements in influencing trade activism.